Previsão hidroambiental integrada do sistema hidrológico do Taim e lagoa Mirim – RS - Paula, Stefany Correia de (2019)
The Taim Wetland (BT), located in the extreme south of Brazil, in a region characterized by recurrence of conflicts over water use, which involve region's main economic activity, flood irrigated rice cultivation, and preservation of the aquatic ecosystem present at the BT. Irrigation water withdrawals are made from Mangueira and Mirim lagoons, located upstream and downstream of BT, respectively. These lagoons regulate BT's water exchange and eventually make it more or less able to accommodate the richness of fauna and flora species that depend on it for their survival throughout or part of their life. Water management in this region is necessary for anticipate or mitigate conflicts of this nature, and hydrological forecasting is one of the tools used to assist decision making. Assuming that it is possible to assess future hydrological conditions, considering the interrelationship of water levels with local fauna and flora, it is possible to estimate the environmental condition for the same horizon as the level forecasts. Thus, this work presents a methodology that allows the realization of the hydro-environmental (hydrological plus environmental) forecast for the BT. The hydrological forecast of the BT levels was performed considering the ensemble forecast in the hydrologic-hydrodynamic cell model, which considers the entire Taim Hydrological System (SHT), including Mangueira Lagoon and the downstream influence condition exerted by Mirim Lagoon on the BT levels, although to a lesser extent than Mangueira Lagoon. As a strategy for forecasting, data from the Atmospheric General Circulation Model (AGCM from CPTEC/INPE), the regional statistical model developed for the Rio Grande do Sul State (MRERS from CCPMet/ UFPel) and historical data were used. The best results were obtained for the methodology that used the historical data, which allowed an ensemble forecast with a 12-month horizon, indicating good results for the proposed methodology. For the environmental forecast were considered previously developed Habitat Suitability Indices (HSI), for nine species bioindicators of the BT. For the use of HSI, an alternative methodology based on Suitability Relationships was developed, without the need to model the forecast of environmental suitability considerin specific hydrological conditions. At the end of the process, the hydrological forecast of the the BT was combined with the Suitability Relationships, allowing the identification of the environmental forecast. The feasibility of applying the methodology was presented by conducting a hydro-environmental forecast for the 2019-2020 crop. The application also highlights the strategies used to circumvent the main difficulty observed in the development of the work, related to the lack of data in the region. Due to the influence of Mirim Lagoon on SHT modeling, it was also necessary to develop a statistical model of level forecast for this lagoon, based on monthly levels, precipitation and evaporation data, simplifying the utilization process. More than one regression model had the adequate ability to estimate Mirim Lagoon levels, especially for smaller forecast horizons, as well as for the purposes of fill lack of data and extension of Mirim's historical series of levels.